Ciało jako metafora Rzeczypospolitej. Analiza semiotyczna „Obrazu szlachcica polskiego” Wacława Kunickiego - Bohuszewicz, Jakub (Litteraria Copernicana, 2008)
An analysis of Kunicki’s opuscule is based on elaborated by semioticians of Tart conception of secondary modeling systems as well as on Louis Hjelmslev’s distinction between a code and a statement. The concepts of a system and a text, as its realization, allow to state the presence of a system of the correspondence between tree levels: a body, some ethical values and a State. The relation of the translation between these three levels constitutes a basic principle of the literary construction of The Picture of Polish Nobleman. However, the relation between the system and the text is of a dynamic character: the text has never been a precise reconstruction of the system of signs. Hence it is interesting to follow the relation between the picture of the social world in the nobleman’s culture and its transformation leading among others to the lack of the gentry status of the nobles in Kunicki’s opuscule.